„Südliches Meer“. Rausch und Ekstase in Gottfried Benns Werk - Eke, Norbert Otto (Benn Forum Band 3 2012/13. Beiträge zur literarischen Moderne [Jahrbuch])

‚Macht nichts, macht nichts, sagte ich mir, macht nichts‘: Herta Müller’s Romanian Novels - Eke, Norbert Otto (Herta Müller)

Widerstehen und Widersprechen [Laudatio auf Herta Müller] - Eke, Norbert Otto (Ehrenpromotion der Fakultät für Kulturwissenschaften der Universität Paderborn an Herta Müller. Paderborn, 29.10.2012. Dokumentation)

„Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur - Eke, Norbert Otto („Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur)

Geklebte Strukturen im Fahrzeugbau – Simulation und Bewertung von Fertigungstoleranzen - Kruschinski, Georg; Matzenmiller, Anton; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson (Leichtbau-Technologien im Automobilbau)

Simulation und Bewertung von Fertigungstoleranzen - Kruschinski, Georg; Matzenmiller, Anton; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artoem; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Georg; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (ACS Nano)

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artoem; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan José; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials)

Oxygen diffusivity in silicon derived from dynamical X-ray diffraction - Will, J.; Gröschel, A.; Kot, D.; Schubert, M. A.; Bergmann, C.; Steinrück, Hans-Georg; Kissinger, G.; Magerl, A. (Journal of Applied Physics)

Experimentieren lernen auf Englisch - geht das? - Ein bilingual ausgerichtetes Chemieprojekt zur Vermittlung des Erkenntniswegs im Film - Fechner, Sabine; Schüttler, Susanne (MNU)

Konzeption und Inbetriebnahme einer neuen Technikumsanlage zur Absorption und Desorption von CO2 - Hüser, Nicole; Kenig, Eugeny

Kartellrecht der Kreditwirtschaft (Syst. VI) - Krimphove, Dieter (Kölner Kommentar zum Kartellrecht Bd. 4)

Kartellrecht der Versicherungswirtschaft (Syst. VI) - Krimphove, Dieter (Kölner Kommentar zum Kartellrecht Bd. 4)

Eigene Innovation oder Zugangsberechtigung zu fremden Innovationen - Krimphove, Dieter (Handbuch Innovationsmanagement)

Ökonomisch/juristische Konzeption der Innovationen - Krimphove, Dieter (Handbuch Innovationsmanagement)

AT 5 der MaComp: Zusammenarbeit mehrere Wertpapierdienstleistungsunternehmen - Krimphove, Dieter (Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen)

AT 7 der MaComp: Das Verhältnis §§ 33 WpHG ff. zu § 25a KWG - Krimphove, Dieter (Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen)

Brain activity in predictive sensorimotor control for landings: an EEG pilot study. - Baumeister, Jochen; von Detten, S; van Niekerk, SM; Schubert, M; Ageberg, E; Louw, QA (Int J Sports Med)

Instrumented anterior mobilization of the ankle joint increases contralateral somatosensory cortex activation in healthy subjects - Needle, AR; Swanik, CB; Schubert, M; Reinecke, K; Higginson, JS; Baumeister, Jochen

Quelltextgenerierung für LEGO Mindstorms-Roboter - Geismann, Johannes (Berichtsband der Informatiktage 2013: Smarte Sichten, smarte Schichten)
Die Komplexität von mechatronischen Systemen wird stetig größer. MechatronicUML (MUML) ist eine Methode zur Entwicklung für Software von mechatronischen Systemen. Im Rahmen einer Bachelorarbeit wurde ein bestehender Quelltextgenerator für MUML-Modelle so erweitert, dass Quelltext für ein Echtzeitbetriebssystem generiert werden kann, welches auf einem LEGO Mindstorms-Roboter installiert ist.

Determinants of market beta: the impacts of firm-specific accounting figures and market conditions - Schlueter, Tobias; Sievers, Sönke (Review of Quantitative Finance and Accounting (VHB-JOURQUAL 3 Ranking B))
This article examines and extends research on the relation between the capital asset pricing model market beta, accounting risk measures and macroeconomic risk factors. We employ a beta decomposition approach that nests competing models with different business risk proxies and allows to frame cross-model comparison. Because model tests require estimated independent variables resulting in measurement error, we empirically estimate three comparable model specifications with instrumental variable estimators and for the first time provide thorough instrument diagnostics in this setting. Correcting for the heretofore neglected weak instruments problem we find that growth risk (i.e., the risk of firm sales variations that are inconsistent with the market wide trends), is the business risk that explains cross-sectional variations in market beta best.
Keywords: CAPM; Cost of capital; Accounting beta; Intrinsic business risk; Growth risk; Instrumental variables

Play-out for Hierarchical Component Architectures - Holtmann, Jörg; Meyer, Matthias (Proceedings of 11th Workshop Automotive Software Engineering)
One approach to cope with the growing complexity of today’s embedded systems software, especially in the automotive domain, is component-based software development. For systems based on hierarchical component architectures like AUTOSAR and developed in conformance with process models such as Automotive SPICE, requirements should be specified for the whole system under development and partitioned subsequently onto the particular components across several hierarchy layers. In previous work, we developed a formal requirements engineering (RE) approach based on a recent Live Sequence Chart (LSC) variant, so-called Modal Sequence Diagrams (MSDs). This scenario-based RE approach allows to validate the requirements by means of simulation (i.e., the play-out algorithm originally conceived for LSCs) and to formally verify the requirements for consistency. However, these scenarios are specified on a plain structural basis that does not reflect the typical structure of component architectures, which are arranged in a hierarchical way and encompass ports, interfaces, and directed connectors. In order to tackle this problem, we introduce in this paper a modeling and simulation approach for MSDs based on hierarchical component architectures. By binding these two aspects together, we foster an integrated and iterative RE and component architecture design.

Modulare Leistungsprognose von Kompaktsteuerungen - Frieben, Jens; Heutger, Henning; Meyer, Matthias; Becker, Steffen (9. Paderborner Workshop Entwurf mechatronischer Systeme)

Sichere Speicherung vertraulicher Daten in verteilten Versionskontrollsystemen - Lass, Michael
Distributed revision control is widespread throughout the software industry. Systems like git and mercurial gained a lot of users over the last years and started to supersede central systems like Subversion or CVS in some projects. While restricting access to those central systems is basically possible, it is difficult to control the propagation of contents in a distributed revision control system because every user has a local copy of the whole repository. In this thesis a concept is developed and implemented that allows secure storage of confidential data in a distributed revision control system and enables users to manage read and write permissions on single confidential files. Therefore different cryptographic methods are used, such as asymmetric encryption, digital signatures and convergent encryption. These techniques are applied in a manner that fits the special requirements of a revision control system and allows a space efficient storage of changes to the encrypted files.

An evaluation testbed for adaptive, topology-aware deployment of elastic applications - Keller, Matthias; Robbert, Christoph; Peuster, Manuel (Proceedings of the ACM SIGCOMM 2013 conference on SIGCOMM)

CROWD: An SDN Approach for DenseNets - Ali-Ahmad, Hassan; Cicconetti, Claudio; de la Oliva, Antonio; Draxler, Martin; Gupta, Rohit; Mancuso, Vincenzo; Roullet, Laurent; Sciancalepore, Vincenzo (2013 Second European Workshop on Software Defined Networks)

A Scalable Redundant TDMA Protocol for High-Density WSNs Inside an Aircraft - Blanckenstein, Johannes; Garcia-Jimenez, Javier; Klaue, Jirka; Karl, Holger (Lecture Notes in Electrical Engineering)

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, P.; Graffi, K. (2013 Conference on Networked Systems)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks -- Workshops)

Denser Networks for the Future Internet, the CROWD Approach - de la Oliva, Antonio; Morelli, Arianna; Mancuso, Vincenzo; Draexler, Martin; Hentschel, Tim; Melia, Telemaco; Seite, Pierrick; Cicconetti, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Enzyklopädie Erziehungswissenschaft Online - Medienpädagogik

Medienpädagogik in Institutionen der Erwachsenen- und Weiterbildung - Kamin, A.-M.; Meister, Dorothee M. (Enzyklopädie Erziehungswissenschaft)

Vermittlung von Medienkompetenz in der Praxis für Kinder und Jugendliche: Schule - Meister, Dorothee M. (Medienkompetenzförderung für Kinder und Jugendliche. Eine Bestandsaufnahme)

Anforderungen an das Lesen in der digitalen Mediengesellschaft - Gerhardts, L.; Meister, Dorothee M. (Zukunft des Lesens. Was bedeuten Generationswechsel, demografischer und technischer Wandel für das Lesen und den Lesebegriff?)

Spiele als Lernköder? Über das Potenzial von Computerspielen - Ganguin, S.; Meister, Dorothee M. (Kinder-Eltern-Medien. Medienpädagogische Anregungen für den Erziehungsalltag)

Medienpädagogische Anregungen für den Erziehungsalltag – Einführende Gedanken - Kamin, A.-M.; Meister, Dorothee M.; Schulte, D. (Kinder- Eltern-Medien)

Lithium niobate dielectric function and second-order polarizability tensor from massively parallel ab initio calculations - Riefer, Arthur; Rohrmüller, Martin; Landmann, Marc; Sanna, Simone; Rauls, Eva; Vollmers, Nora Jenny; Hölscher, Rebecca; Witte, Matthias; Li, Yanlu; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (High Performance Computing in Science and Engineering ‘13)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe–Salpeter equation yield a dielectric function for the stoichiometric material that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are at least partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that self-energy effects improve the agreement between experiment and theory. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular for the 21 and 31 tensor components, further improving the agreement with measured data.

HOMO band dispersion of crystalline rubrene: Effects of self-energy corrections within the GW approximation - Yanagisawa, Susumu; Morikawa, Yoshitada; Schindlmayr, Arno (Physical Review B)
We investigate the band dispersion and relevant electronic properties of rubrene single crystals within the GW approximation. Due to the self-energy correction, the dispersion of the highest occupied molecular orbital (HOMO) band increases by 0.10 eV compared to the dispersion of the Kohn-Sham eigenvalues within the generalized gradient approximation, and the effective hole mass consequently decreases. The resulting value of 0.90 times the electron rest mass along the Γ-Y direction in the Brillouin zone is closer to experimental measurements than that obtained from density-functional theory. The enhanced bandwidth is explained in terms of the intermolecular hybridization of the HOMO(Y) wave function along the stacking direction of the molecules. Overall, our results support the bandlike interpretation of charge-carrier transport in rubrene.

A material-based quality concept for polymer laser sintering - Josupeit, Stefan; Rüsenberg, Stefan; Schmid, Hans-Joachim (24th Annual International Solid Freeform Fabrication Symposium)
In this work, the quality of laser sintered parts is investigated along a defined process chain for a nylon 12 material (PA 2200) on an EOSINT P395 laser sintering system. Important influencing factors are figured out. Rheological powder characterization methods are investigated as well as mechanical, physical and other chosen part properties. The concept allows reproducible part quality characteristics and is used to obtain (testing) temperature dependent material data. It can also be extended on further materials based on nylon 12: PA 2241 FR, which is convenient for the aircraft industry due to its flame-retardant properties, and PA 2221, which has economic advantages due to a lower material consumption.

Advanced characterization method of Nylon 12 materials for application in laser sinter processing - Rüsenberg, Stefan; Schmid, Hans-Joachim (International Conference of the Polymer-Processing-Society (PPS))
Laser Sintering is a powder based additive manufacturing technology. The amount of used powder, which is not sintered, can be refreshed and used for further building jobs. Due to cost reduction, better mechanical properties and a simpler processing it is reasonable to combine virgin and used powder for part manufacturing. During the building time the powder is thermally loaded and its structure is changed. State of the art in laser sintering is a defined powder ratio. Since the powder ageing depends on the individual history of sintering, this procedure cannot ensure a defined powder quality. However, for a serial production it is necessary to characterize the raw material, as well as all other steps along the process chain, in order to ensure a high reproducibility and reliability. Rheological, physical and particle properties are considered to correlate powder and chosen material properties. Different powder qualities adjusted by the Melt Volume Rate (MVR) are tested using promising rheological properties like viscosity or molecular weight. Investigations about powder bed density, bulk properties as well as thermal characterization complement the experimental setup. These parameters are correlated with mechanical, electrical, thermal and physical material properties of laser sintered parts. The most important influencing factors along the process chain are kept constant. At the end a procedure is shown to obtain a defined powder quality. This procedure will be transferred to other materials and will be tested using other laser sintering machines of the same type as well as other types.

Mechanische und rheologische Untersuchungen neuer Laser Sinter Materialien - Josupeit, Stefan; Rüsenberg, Stefan; Schmid, Hans-Joachim (Merseburger Rapid Prototyping Forum)

Additiv versus Konventionell: Benchmarking am Beispiel eines Designs aus der Luftfahrtindustrie - Rüsenberg, Stefan; Bagsik, A.; Büsching, J.; Schmid, Hans-Joachim (RapidTech)

Design for additive manufacturing - Adam, Guido; Zimmer, Detmar

Konstruktionsregeln für additive Fertigungsverfahren - Adam, Guido; Zimmer, Detmar (Konstruktion)
Additive Fertigungsverfahren stellen Bauteile und Baugruppen aus Kunststoff- oder Metallwerkstoffen schicht¬weise, ohne formgebendes Werkzeug her. Daraus resultierende Gestaltungsmöglichkeiten schaffen einen großen Nutzen für Anwender dieser Technologie. Um diesen Nutzen einem breiten An-wenderkreis zugänglich zu machen, werden im Projekt „Direct Manufacturing Design Rules“ (DMDR) Konstruktionsregeln für Additive Fertigungsverfahren erarbeitet. Hierzu wird zunächst eine verfahrens-unabhängige Methode zur Erarbeitung der Konstruktionsregeln entwickelt. Diese ermöglicht die Erar-beitung von Konstruktionsregeln, die zunächst für die hier betrachteten Additiven Fertigungsverfahren und Werkstoffe gelten. Die Ergebnisse werden in einem Konstruktionsregelkatalog zusammengefasst.

Die Potentiale additiver Fertigung nutzen - Adam, Guido

Konstruktionsregeln für additive Fertigungsverfahren - Ausbildung, Lehre - Adam, Guido

Ökonomisch-ökologische Bewertung von elektromechanischen Antriebssystemkonzepten. Ein Werkzeug zur schnellen und wirtschaftlichen Konzipierung optimaler Antriebssysteme für spezifische Anwendungen - Zimmer, Detmar; Klause, Alexander (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Multiobjective Optimization including Safety of Operation Applied to a Linear Drive System - Meyer, Tobias; Hölscher, Christian; Menke, Michael; Sextro, Walter; Zimmer, Detmar (PAMM - Proceedings in Applied Mathematics and Mechanics)

Energetische Optimierung eines Mehrmotorenantriebssystems für Kautschukinnenmischer - Hölscher, Christian; Michaelis, Stefanie; Strop, Malte; Zimmer, Detmar

Situationsbezogene Luftspaltoptimierung am Linearmotor eines schienengebundenen Fahrzeugs - Schmidt, Alexander

Beitrag zur Geräuschminderung an Federkraftbremsen - Wecker, Markus

AutASS - Autonome Antriebstechnik durch Sensorfusion für die intelligente, simulationsbasierte Überwachung & Steuerung von Produktionsanlagen“ Teilvorhaben: „Beanspruchungs- und Lastkollektivbestimmung“ - Lessmeier, Christian; Kürpick, Markus; Zimmer, Detmar

Performance Analysis of Self-Adaptive Systems for Requirements Validation at Design-Time - Becker, Matthias; Luckey, Markus; Becker, Steffen ({Proceedings of the 9th ACM SigSoft International Conference on Quality of Software Architectures (QoSA)})
Self-adaptation allows continuously running software systems to operate in changing and uncertain contexts while meeting their requirements in a broad range of contexts, e.g., from low to high load situations. As a consequence, requirementsfor self-adaptive systems are more complex than requirements for static systems as they have to explicitly address properties of the self-adaptation layer.While approaches exist in the literature to capture this new type of requirements formally, their achievement cannot be analyzed in early design phases yet. In this paper, we apply RELAX to formally specify non-functional requirements for self-adaptive systems. We then apply our model-based SimuLizar approach for a semi-automatic analysis to test whether the self-adaptation layer ensures that these non-functional requirements are met. We evaluate our approach on the design of a proof-of-concept load balancer system. As this evaluation demonstrates, we can iteratively improve our system design by improving unsatisfactory self-adaption rules.

SimuLizar: Design-Time modeling and Performance Analysis of Self-Adaptive Systems - Becker, Matthias; Becker, Steffen; Meyer, Joachim ({Proceedings of the Software Engineering (SE)})
Modern software systems adapt themselves to changing environments, to meet quality-of-service requirements, such as response time limits. The engineering of the system's self-adaptation logic does not only require new modeling methods, but also new analyzes of transient phases. Model-driven software performance engineering methods already allow design-time analysis of steady states of non-adaptive system models. In order to validate requirements for transient phases, new modeling and analysis methods are needed. In this paper, we present SimuLizar, our initial model-driven approach to model self-adaptive systems and analyze the performance of their transient phases. Our evaluation of a load balancer toy example shows the applicability of our modeling approach. Additionally, a comparison of our performance analysis with a prototypical implementation of our example system shows that the prediction accuracy is sufficient to identify unsatisfactory self-adaptations.

Mehr Theorie wagen: Eine neue Ausbildung für die Praxis? - Sureth-Sloane, Caren (WiSt - Wirtschaftswissenschaftliches Studium)

Intelligenz in der Produktion - Spitzencluster it's OWL als Wegbereiter für Industrie 4.0 - Dumitrescu, Roman; Kühn, Arno (Markt&Technik Summit Industrie 4.0, München, 16. - 17. Okt. 2013)

Von der Anforderungserfassung bis zur Funktionsstruktur - Ein Systems Engineering-Vorgehen für die industrielle Praxis - Schmitt, Nicolas; Kaiser, Lydia; Dumitrescu, Roman; Hofmann, Maik (Tag des Systems Engineering)

Hybrid-Actuated Finger Prosthesis with Tactile Sensing - Low, Cheng Yee; Kasim, Mohamad Amlie Abu; Koch, Torben; Dumitrescu, Roman; Yussof, Hanafiah; Jaafar, Roseleena; Jaafar, Ahmed; Aqilah, Ahsana; Ng, Kok Mun (International Journal of Advanced Robotic Systems)

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Journal of Production Engineering Research & Development (PERE) 7)

Coordination of Multiple Autonomous Intersections by Using Local neighborhood information - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. IEEE International Conference on Connected Vehicles and Expo)

Automated Design of an Unscented Kalman Filter for State- and Parameter Estimation on unknown Models - Schweers, Christoph; Trächtler, Ansgar; Kruse, Daniel (Control, Automation, Robotics & Embedded Systems)

Vehicle to Infrastructure based Safe Trajectory Planning for Autonomous Intersection Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. IEEE International Conference on ITS Telecommunication (ITST))

Dynamical Model of Ball Juggling Delta Robots using Reflection Laws - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Lankeit, Christopher; Trächtler, Ansgar (16th International Conference on Advanced Robotics (ICAR))

Erstellung von Prozessmodellen für den Entwurf selbst-optimierender Regelungen - Kessler, Jan Henning; Gausemeier, Jürgen; Iwanek, Peter; Köchling, Daniel; Krüger, Martin; Trächtler, Ansgar (Internationales Forum Mechatronik 2013)

Scientific Automation rises the productivity of production facilites - Frank, Ursula; Anacker, Harald; Bielawny, Dirk (Digital Product and Process Development Systems)

2-DOF State Control Scheme for the Motion Control of a Parallel Kinematic Machine - Flottmeier, Sarah; Trächtler, Ansgar (Proceedings of the 2nd International Conference on Control and Fault-Tolerant Systems)

Methoden zur Einbindung von Fehlersimulationen in die XiL-Techniken - Fast, Viktor; Kruse, Daniel; Schweers, Christoph; Trächtler, Ansgar (Virtuelle Instrumente in der Praxis (VIP 2013))

Online-Zustands- und Parameterschätzung an Dymola-Modellen auf NI-Echtzeithardware - Schweers, Christoph; Kruse, Daniel; Fast, Viktor; Trächtler, Ansgar (Virtuelle Instrumente in der Praxis (VIP 2013))

Trajectory Optimization and Optimal Control of Vehicle Dynamics under Critically Stable Driving Conditions - Khatab, Shaady; Trächtler, Ansgar (IEEE International Conference on System Science and Engineering (ICSSE))

Discrete Objective-based Control for Self-Optimizing Systems - Krüger, Martin; Remirez, Andria; Kessler, Jan Henning; Trächtler, Ansgar (The 2013 American Control Conference)

Closed-Loop Control with Optimal Tire-Force Distribution for the Horizontal Dynamics of an Electric Vehicle with Single-Wheel Chassis Actuators - Reinold, Peter; Trächtler, Ansgar (2013 American Control Conference)

Modellbasierter Entwurf geregelter Federungssysteme fur Laufwerke gepanzerter Kettenfahrzeuge - Anwendungsbeispiele und Potenziale - Kradepohl, Ulrich; Gense, Alexander (AUTOREG 2013: Steuerung und Regelung von Fahrzeugen und Motoren)

Integrierter Regelungs- und Softwareentwurf für komplexe mechatronische Systeme - Dziwok, Stefan; Just, Viktor; Schierbaum, Thomas; Schäfer, Wilhelm; Trächtler, Ansgar; Gausemeier, Jürgen; Pohlmann, Uwe; Schäfer, Wilhelm; Suck, Julian; Sudmann, Oliver; Tichy, Matthias (9. Paderborner Workshop Entwurf mechatronischer Systeme)

Modellbasierte Entwicklung eines neuartigen Heizverfahrens für Waschautomaten - Kruse, Daniel; Trächtler, Ansgar (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Optimale Umschaltstrategien bei Aktorausfall mit Pfadverfolgungstechniken - Timmermann, Robert; Horenkamp, Christian; Dellnitz, Michael; Kessler, Jan Henning; Trächtler, Ansgar (9. Paderborner Workshop Entwurf mechatronischer Systeme)

Beobachterbasierte Regelung von Parallelkinematiken in kartesischen Koordinaten - Flottmeier, Sarah; Trächtler, Ansgar (Tagungsband Mechatronik 2013)

Entwurf eines Unscented-Kalman Filters zur Zustands- und Parameterschätzung an Dymola-Modellen - Schweers, Christoph; Kruse, Daniel; Trächtler, Ansgar (VDI Mechatronik)

Methodik zur anforderungsgerechten Wahl der Modellierungstiefe von Verhaltensmodellen fuer die virtuelle Inbetriebnahme - Schmuedderich, Tanja; Lochbichler, Matthias; Trächtler, Ansgar (Tagungsband Mechatronik 2013 (ISBN 3-86130-958-0))

Procedural Model for the Virtual Commissioining on the Basis of Model-based Design - Schmuedderich, Tanja; Trächtler, Ansgar; Brökelmann, Jan; Gausemeier, Jürgen (Smart Product Engineering - Proceedings of the 23rd CIRP Design Conference (ISBN 978-3-642-30816, Springer-Verlag))

Approach for an Early Validation of Mechatronic Systems using Idealized Simulation Models within the Conceptual Design - Bauer, Frank; Gausemeier, Jürgen; Köchling, Daniel; Oestersötebier, Felix (Smart Product Engineering - Proceedings of the 23rd CIRP Design Conference)

Active Suspension Module - Kessler, Jan Henning; Trächtler, Ansgar (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Increasing the Dependability of Self-Optimizing Systems During Operation Using the Multi-Level Dependability Concept - Kessler, Jan Henning; Meyer, Tobias; Sextro, Walter; Sondermann-Wölke, Christoph; Trächtler, Ansgar (Dependability of Self-Optimizing Mechatronic Systems)

Increasing Intelligent Systems’ Reliability by using Reconfiguration - Meyer, Tobias; Kessler, Jan Henning; Sextro, Walter; Trächtler, Ansgar (The Annual Reliability and Maintainability Symposium (RAMS))

Virtual Test Driver for Critically Stable Driving Maneuvers - Khatab, Shaady; Trächtler, Ansgar (IEEE Conference on Intelligent Transportation Systems (ITSC))

Modelling of an Active Suspension for the All-Terrain Vehicle and an Estimation of Possibility of its Use to Reduce the Load on a Wheel with the Damaged - Poddubny, Wladimir; Trächtler, Ansgar; Jäker, Karl-Peter; Harchenko, Jewgenij; Warkentin, Andreas P. (Мехатроника, Автоматизация, Управление (Mechatronik, Automatisierung, Regelung))

Autonomously Driven Railway Cabin Convoys - Communication, Control Design and Experimentation - Henke, Christian; Trächtler, Ansgar (International Conference on Connected Vehicles & Expo (ICCVE))

Regelungstechnik - Föllinger, Otto; Konigorski, Ulrich; Lohmann, Boris; Roppenecker, Günter; Trächtler, Ansgar

ContainerRailCab - Die Alternative zum LKW-Transport im Hamburger Hafen - Trächtler, Ansgar; Gockel, Franz-Barthold; Rustemeier, Carsten (ForschungsForum Paderborn)

X-by-Wire Test Vehicle - Reinold, Peter; Trächtler, Ansgar (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Dependability-oriented Multiobjective Optimization - Reinold, Peter; Sextro, Walter; Sondermann-Wölke, Christoph; Trächtler, Ansgar (Dependability of Self-Optimizing Mechatronic Systems)

Applications of Self-Optimizing Systems - Hölscher, Christian; Kessler, Jan Henning; Meyer, Tobias; Rasche, Christoph; Reinold, Peter; Sextro, Walter; Sondermann-Wölke, Christoph; Zimmer, Detmar (Dependability of Self-Optimizing Mechatronic Systems)

Impact and Influence Factors of Additive Manufacturing on Product Lifecycle Costs - Lindemann, C.; Jahnke, U.; Moi, M.; Koch, R. (24th Annual International Solid Freeform Fabrication Symposium)
At first sight the direct costs of Additive Manufacturing (AM) seem too high in comparison to traditional manufacturing. Considering the whole lifecycle costs of parts changes the point of view. Due to the modification of the new production process and new supply chains during a parts lifecycle, producing companies can strongly benefit from AM. Therefore, a costing model for assessing lifecycle costs with regard to specific applications and branches has been developed. The costing model represents the advantages of AM monetarily. For the evaluation of this model and the influence factors, different case studies have been performed including different approaches in part redesign. Deeper research is and will be carried out with respect to the AM building rates and the comparability of various AM machines, as these facts are hardly comparable for end users. This paper will present the methodology and some results of the case studies conducted over the whole product lifecycle.

The Need to Start Research Education Early - Joel, W. J. (IEEE Computer Graphics and Applications)

Information Visualization Courses for Students with a Computer Science Background - Kerren, A. (IEEE Computer Graphics and Applications)

Building Virtual Worlds Carrying on the Legacy of Randy Pausch's "Head Fake" - Schell, J.; Klug, C. (IEEE Computer Graphics and Applications)

The benefits of comics for language learning at the lower secondary level: A practical approach - Rumlich, Dominik (Teaching comics in the foreign language classroom)

Students’ general English proficiency prior to CLIL: Empirical evidence for substantial differences between prospective CLIL and non-CLIL students in Germany - Rumlich, Dominik (Content and language integrated learning (CLIL) in Europe)

Using comics in the classroom - The obvious way of creating a favourable learning environment? - Deane, Neil; Rumlich, Dominik (Medien und Interkulturalität im Fremdsprachenunterricht: Zwischen Autonomie, Kollaboration und Konstruktion)

A Variational Approach to Modeling Slow Processes in Stochastic Dynamical Systems - Noé, Frank; Nüske, Feliks (Multiscale Modeling & Simulation)